Robotisation et assurance - Dumont, Monique (Assurances)

(untitled) (HEC Montréal, 1983)
More and more, robots will be replacing humans in their more basic tasks. The Japanese in particular have produced in-depth studies in the use of robots. In the United States, attempts are being made to replace man by machine. ln the past, whole mechanical units were in use whereas today, there is a more frequent use of robots for activation and direction of machines. The robot handles the automatic start-up of production. This is the subject of Miss Dumont's article although the present shortage of documentary evidence on the subject of robots is obviously reflected in this article.